2013
DOI: 10.1371/journal.pone.0078051
|View full text |Cite
|
Sign up to set email alerts
|

Bupleurum Polysaccharides Attenuates Lipopolysaccharide-Induced Inflammation via Modulating Toll-Like Receptor 4 Signaling

Abstract: Background Bupleurum polysaccharides (BPs), isolated from Bupleurum smithii var. parvifolium, possesses immunomodulatory activity, particularly on inflammation. Bacterial endotoxin lipopolysaccharide (LPS) triggers innate immune responses through Toll-like receptor 4 (TLR4) on host cell membrane. The present study was performed to evaluate whether the therapeutic efficacy of BPs on suppression of LPS’s pathogenecity could be associated with the modulating of TLR4 signaling pathway.Methodology/Principal Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 40 publications
(56 reference statements)
1
19
0
Order By: Relevance
“…Moreover, the increase of TRAF6 by TNF-α and IL-1β was very rapid (15 min). In agreement with our results, Wu et al showed that TRAF6 was significantly increased at 15 min after incubation with lipopolysaccharides in macrophages [51]. The rapid induction of TRAF6 may be attributed to translational regulation, which needs to be investigated in the future.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the increase of TRAF6 by TNF-α and IL-1β was very rapid (15 min). In agreement with our results, Wu et al showed that TRAF6 was significantly increased at 15 min after incubation with lipopolysaccharides in macrophages [51]. The rapid induction of TRAF6 may be attributed to translational regulation, which needs to be investigated in the future.…”
Section: Discussionsupporting
confidence: 92%
“…reported by other compounds, such as inosine, 14 bupleurum polysaccharides, 21 proxylin A, 22 and quercetin, 23 and by other pyrrol compounds, such as T-686, an inhibitor of plasminogen activator inhibitor-1 that was associated with a mortality reduction in mice exposed to LPS. 24 However, none of those compounds had described any antiapoptotic activity in sepsisinduced lung injury.…”
Section: Inhibition Of Lps-induced Airway Cell Injury Ne Cabrera-benímentioning
confidence: 92%
“…Thereafter, they were washed three times in PBS (5 min/wash) and incubated with a 1:200 dilution of secondary antibody (fluorescein isothiocyanate [FITC]-conjugated goat anti-mouse IgG) for 1 h at 37°C. The nuclei were stained using DAPI (0.25 g/ml; Life Technologies), and the staining was visualized using a confocal laser-scanning microscope (LSM510; Carl Zeiss, Gottingen, Germany) (26).…”
Section: Neutralization Of Lpsmentioning
confidence: 99%